(untitled) (Orfeu, 2022)
In this article, a compositional work plan, of a pedagogical nature, is described, based on the theoretical contents of the six chapters of Straus’s (2013) book, entitled Introduction to Post-Tonal Theory. The central idea was to demonstrate the planning, the composition, and the subsequent concatenation of six independent fragments, with the active participation of five composition students, focusing on the following topics: interval types, sets classes, operations on pitch-class sets, contour relations, Z-relation, scalar formations, dodecaphonism, combinatoriality, derivation, multiplication, and integral serialism. Concomitant with the post-tonal theoretical framework, five original pedagogical premises served as a guide during each stage of the work. The six fragments, each with approximately thirty seconds, were then concatenated, taking into account six original procedures proposed by the author, in order to produce a coherent work of about three minutes, for wind quintet.